AKULTURASI NILAI BUDAYA MELAYU DAN BATAK TOBA PADA MASYARAKAT MELAYU KOTA TANJUNGBALAI ASAHAN - Mailin Mailin (State Islamic University North Sumatra, 2017)
Abstract: This paper attempts to analyze the acculturation process of Malays and Toba Batak cultures in Asahan Tanjungbalai, and to what extent the Sultan of Asahan influenced the process of acculturation. This study uses descriptive qualitative research method. The findings of this research showed that the process of acculturation Malay and Muslim Toba Batak culture in the city emerged from the government of Tanjungbalai Sultan Asahan I who ruled in the city before the independence era of the Republic of Indonesia. Religious leaders (ulama) and traditional leaders also played a role in the acculturation process of Malay cultural values in Tanjungbalai, especially in the Batak Toba ethnic Muslim milieu. Acculturation between these two cultures gave birth to a Malay culture which led to a different characteristic to the Malay culture in the archipelago. The author affirms that Malays in the city, by nature, tends to be tough in character as a result of Toba Batak ethnic character. Abstrak: Acculturation of the Malay and Toba Batak Cultural Values on Malay Societies in Tanjung Balai City Asahan North Sumatra. Penelitian ini adalah penelitian lapangan yang bertujuan untuk mengetahui proses akulturasi budaya Melayu dan Batak Toba di Tanjungbalai Asahan, serta seberapa besar pengaruh Sultan Asahan dalam proses akulturasi budaya Melayu dan Batak Toba di Asahan. Penelitian ini menggunakan metode penelitian kualitatif deskriptif. Hasil penelitian menunjukkan bahwa proses akulturasi budaya Melayu dan budaya Batak Toba Muslim di kota Tanjungbalai berawal dari pemerintah Sultan Asahan I yang memerintah di kota Tanjungbalai sebelum kemerdekaan Negara Republik Indonesia. Tokoh agama (ulama) dan tokoh adat juga turut berperan dalam proses akulturasi nilai budaya Melayu di Kota Tanjungbalai, khususnya pada etnis Batak Toba Muslim. Akulturasi antar dua budaya ini melahirkan sebuah budaya Melayu yang memiliki ciri khas yang berbeda dengan budaya Melayu di Nusantara. Melayu di kota ini memiliki sifat serta karakter yang cenderung kasar dan keras, seperti karakter etnis Batak toba. Kata Kunci: Melayu, Batak Toba, Kesultanan Asahan, Islam